Analisis Faktor Makro Ekonomi Yang Mempengaruhi Penerimaan Zakat, Infak, dan Shadaqah di Indonesia Tahun 2005-2019 - Dharma Yanti; Tika Parlina (Borneo Islamic Finance and Economics Journal, 2022)
This study aims to determine the macroeconomic factors that affect the acceptance of Zakat, Infaq and Sadaqah in Indonesia. This study uses quantitative research methods with path analysis. The independent variables in this study are the rate of economic growth, number of working population, GDP/capita, provincial minimum wage. While the dependent variable is the amount of zakat, infaq and shadaqah receipts. The results showed that all variables had a significant effect on the acceptance of zakat, infaq, and shadaqah. However, after going through path analysis, it is known that the rate of economic growth (X1) and GDP/capita (X3) has a negative and significant effect on zakat, infaq, and shadaqah receipts, while the number of working population (X2) and the provincial minimum wage (X4) have an influence. positive and significant to the acceptance of Zakat, Infaq, and Sadaqah. Keywords : Zakat, Infaq, Shadaqah, Economic Growth, GDP.